Patterns of care and survival outcomes for laryngeal small cell cancer. Issue 3 (10th December 2018) - Lin, Alexander J.; Gabani, Prashant; Fischer‐Valuck, Ben; Rudra, Soumon; Gay, Hiram; Daly, Mackenzie; Oppelt, Peter; Jackson, Ryan; Rich, Jason; Paniello, Randal; Zevallos, Jose; Adkins, Douglas; et al.
Abstract: Background: To determine practice patterns and outcomes of laryngeal small cell cancer (LSCC) across the United States. Methods: Patients with LSCC were identified in the National Cancer Database. Overall survival (OS) was compared with Kaplan‐Meier analysis and Cox regression. Results: From 2004 to 2014, the 5‐year OS for early stage (n = 47), locally advanced stage (n = 133), and metastatic disease (n = 53) was 34%, 26%, and 9%, respectively. Chemoradiation was given in 66% of cases. Chemotherapy was less likely given in early stage disease ( P  = .001), and definitive radiation was less likely given in metastatic disease ( P  < .001). Definitive radiation improved median OS in locally advanced LSCC (20 vs. 7 months, log‐rank P  = .04). In multivariable modeling, radiation dose ≥40 Gy was associated with better OS ( P  < .001). Conclusion: Chemoradiation was the most common practice for treating locally advanced LSCC, and radiation dose ≥40 Gy was associated with improved OS.